Optimization of health promotion through audiovisual media and leaflets to increase adolescents' awareness of breast self-examination - Nurafriani Nurafriani; Sumarmi Sumarmi; Risna Ayu Rahmadani; Yoga Tri Wijayanti; Indrawati Aris Tyarini (Edukasi Ilmiah Indonesia, 2025)
This community service activity aimed to optimize health promotion to increase adolescents' awareness of breast self-examination (BSE) using audiovisual media and leaflets. The implementation methods included interactive counselling, the presentation of educational audiovisual materials, and the distribution of informative leaflets designed to meet the needs of the target adolescent audience. The activities were carried out in collaboration with schools and youth communities using an engaging and accessible approach. The results showed an increase in participants' understanding of the importance of BSE, the correct techniques for performing it, and its role in the early detection of breast abnormalities. Based on participant feedback, the combination of audiovisual media and leaflets proved effective in capturing attention and simplifying complex information. In conclusion, the use of audiovisual media and leaflets is an effective approach to raising adolescents' awareness of BSE. This approach provides a practical and engaging method for delivering health education, making it a valuable strategy for promoting preventive health behaviours among adolescents.